Studying the plant cover's changes in AL hassakeh province by using satellite images - Eid, Safieh; ALwesh, Yara (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This research shows the importance of using remote sensing techniques in the study of vegetation changes due to the speed of these technologies, the accuracy, comprehensiveness and saving effort and money. Using change detection methods and applicant it on the normalized difference vegetation index which is taken from Modis vegetation index images led us to know the case of the plant and it's spread has resulted in the studied area. Where the vegetation changes can be monitored with the passage of times, depending on the technology of remote sensing by the preparation of data bases which benefit in knowing the case of the plant as well as it's useful in the development of data base for the completion of periodic monitoring programs for the investment and management of natural resources.